Relationship between Self Adjustment and Social Cohesion of Multiethnic Students in Dharmasraya District High School - Yuliani, Vivi; Firman, Firman (Current Issues in Counseling, 2021)
Self-adjustment is an individual's ability to be able to live and get along with his environment. This study aims to describe students' self-adjustment and social cohesion and examine the relationship between self-adjustment and students' social cohesion. This type of research is descriptive correlational. The population of this study was 208 students who were registered in the 2021/2022 academic year with a sample of 137 students, the sample was drawn using the Proportional Random Sampling technique. Collecting data using a self-adjustment questionnaire and a student social cohesion questionnaire with a Likert Scale model. The data were processed using descriptive statistical analysis techniques and to test the relationship the data were analyzed using the Pearson Product Moment formula with SPSS version 20.0. The results showed: (1) the level of student adjustment was in the low category with a percentage of 60.7%, (2) the level of student social cohesion was in the low category with a percentage of 65.0%, (3) there was a significant and positive relationship between adjustment with students' social cohesion with a large correlation of 0.983 which is in the weak category and a significance of 0.000.